Ice-shelf vibrations modeled by a full 3-D elastic model (Version#5) ... - Konovalov, Yuri V. (Zenodo, 2023)
This version contains a model (description and code) developed for modeling ice shelf vibrations and based on the finite volume method applied to discretize the momentum equations and the wave equation (for under-ice seawater in a cavity). ...